Role of lycopene in the prevention of oral precancerous lesions. A review - Shetty, Shishir Ram; Al-bayati, Sura Ali Ahmed Fuoad; Hamed, Mohammed Said; Abdemagyd, Hossam Abdelatty Eid (The European Research Journal, 2017)
Objective. To systematically review the methodology and results of clinical trials conducted on oral precancer patients using lycopene. Methods. An internet search using google search engine including key words -’’lycopene, oral submucous fibrosis oral leukoplakia and oral cancer’’- was done Full text articles in English language of all the clinical trials that were published in journals from the year 2004 to 2016 were obtained and evaluated. Results. The data available from the clinical trials were analyzed and presented under broad headings of sample size, duration of study, dosage and results and presented in tabular form. Conclusions. Lycopene is a promising candidate in reducing cancer and oral diseases in human beings. This review discusses the benefits of lycopene in prevention of different oral diseases.